KINERJA UMKM DITINJAU DARI BUDAYA ORGANISASI, ORIENTASI KEWIRAUSAHAAN, MANAJEMEN KUALITAS TOTAL, DAN MODAL SOSIAL - Devi Ayu Lestari; Enni Savitri; Riska Natariasari (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2021)
This study aims to examine the effect of Organizational Culture, Entrepreneurship Orientation, Total Quality Management, and Social Capital on Business Performance. The population in this study was Micro, Small, and Medium Enterprises (MSMEs) engaged in processing industry in sub-district of Tampan Pekanbaru city. This study uses census method in sampling with owner of Micro, Small, and Medium Enterprises (MSMEs) in sub-district of Tampan Pekanbaru city as the respondent amount 122 unit enterprises. The data used in this study are primary data with questionnaires as an instrument. The data analysis method used is Structural Equation Model-Partial Last Square (SEM-PLS) by using WarpPLS 6.0 software. The results of this study showed that Organizational Culture, Entrepreneurship Orientation, Total Quality Management, and Social Capital have an effect on Business performance. The results indicate the important role Organizational Culture, Entrepreneurship Orientation, Total Quality Management, and Social Capital in improving the performance of MSMEs.